A global response roadmap to the asteroid impact threat: The NEOShield perspective. (1st December 2015) - Perna, D.; Barucci, M.A.; Drube, L.; Falke, A.; Fulchignoni, M.; Harris, A.W.; Harris, A.W.; Kanuchova, Z.
Abstract: Besides being of great scientific interest, near-Earth objects represent a well-founded threat to life on our planet. Nonetheless, up to now there has been no concerted international plan on how to deal with the impact threat, and how to prepare and implement mitigation measures. The NEOShield project is funded by the European Commission to address such issues, to investigate the feasibility of techniques to prevent a potentially catastrophic impact on Earth by an asteroid or a comet, and to develop detailed designs of appropriate space missions to test deflection techniques. In this work we present and discuss the scientific and strategic aspects of the asteroid impact threat, highlighting the necessary steps so as to be ready to react to future hazardous objects. Abstract : Highlights: We present our latest estimates of the NEO population and of impact consequences. We highlight the activity and results of the European NEOShield programme. We review ongoing and future international efforts in impact risk mitigation. We highlight the next steps so as to be ready to react to future hazardous objects.